A NOVEL APPROACH FOR IMPROVING THE QUALITY OF SERVICE FOR WIRELESS VIDEO TRANSCODING - AHMAD, ASHRAF M. A.; LEE, SUH-YIN (Journal of Mobile Multimedia, 2006)
To deliver streaming video over wireless networks is an important component for most interactive multimedia applications running on personal wireless handset devices. Such personal devices should be inexpensive, compact, and lightweight. Wireless channels have limited bandwidth and a high channel bit error rate. Delay variation of packets due to network congestion with the high bit error rate lessens the quality of video at the handheld device. Therefore, mobile access to multimedia content requires video transcoding functionality at the edge of the mobile network for interworking with heterogeneous networks and services. Under certain conditions, the bandwidth of a coded video stream needs to be drastically reduced. We propose a cost-efficient mechanism for improving the quality of service (QoS) delivered to the mobile user, by introducing a robust and efficient transcoding scheme as proven by extensive experiments. The proposed approach refines the motion vectors value without the need to re-perform the motion estimation process. Then the transcoding mechanism will be preformed using the new fine motion vectors. Thus, great amounts of computing resources have been saved. Exceptional performance is demonstrated in the experiment results, as these experiments were designed to verify and prove the robustness of the proposed approach.